Successful diagnosis of Turner syndrome in a 1-year-old girl during laparoscopic percutaneous extraperitoneal closure - Yohei Sanmoto; Shunji Kinuta (Elsevier, 2023)
A 1-year-old girl was referred to our hospital with swelling in the left inguinal region. Her medical history included an unexplained short stature and growth failure. Physical examination revealed a left indirect inguinal hernia, and she underwent laparoscopic percutaneous extraperitoneal closure (LPEC). Laparoscopic examination revealed streak gonads on the bilateral ovaries and a relatively small uterus. Based on the intraoperative findings, disorders of sex development (DSDs) were strongly suspected, and chromosomal analysis (G-band) was performed. Her karyotype was 45,X/46 XX, suggesting mosaic Turner syndrome. According to the literature, DSD is found in approximately 1% of female patients with inguinal hernia. Although it is sometimes difficult to use conventional techniques, LPEC allows for easy observation of the internal genitalia and is useful for early detection of DSDs.